KARAKTERISTIK KOMITE AUDIT, STRUKTUR KEPEMILIKAN DAN FINANCIAL DISTRESS - Sari, Mayang; Husaini, Husaini (JURNAL FAIRNESS, 2016)
This study aims to determine the effect of audit committee characteristics and ownership structure on financial distress. Audit committee characteristics used in this study is the independence of the audit committee, audit committee expertise, audit committee size and the frequency of audit committee meetings while the ownership structure used this study is institutional ownership and managerial ownership.The population of non-financial companies listed on the Indonesia Stock Exchange in 2010-2011. Based on purposive , there are 364 samples consist of 294 financially distressed firms and 70 financially distressed firms. Criteria of financial distress in this study viewed from a negative net profit two years in a row. While non-financial criteria of distress seen positive net profit two years in a row and for more than one year of dividend payments . Data analysis using logistic regression with SPPS 16 .The analysis showed that the expertise of the audit committee and audit committee meeting frequency is significantly negative effect on financial distress.